(untitled) (Scientific journal of the Fergana State University, 2023)
The purpose of the article is to examine various approaches and methods for assessing the quality of Education. The article analyzes the importance of assessment in the educational system, its concept and objectives. For this purpose, the following research methods were used: self-assessment, cross-evaluation, reflection. According to the results of the study, it has been shown that students ’ interest in the lessons will increase, personal results will be formulated, the scope of thinking and the desire to acquire information independently. The conclusion was drawn to the fact that the methodological recommendations developed for the organization of internal monitoring of the quality of education in an educational institution contribute to the qualitative assessment of Education.